Pulmonary immune responses induced in BALB/c mice by Paracoccidioides brasiliensis conidia (2008)
ABSTRACT : Knowledge concerning the host–Paracoccidioides brasiliensis interactions is abundant. Yet, most of the experimental studies have used yeast cells to prepare the corresponding inoculum. As these cells do not represent the naturally infecting propagules, the corresponding experiments by-pass the earlier stages of such interactions. Studies done in patients, who also harbour yeast cells, suffer from the same bias. The review presented below focuses on the immune responses of BALB/c mice infected with conidia obtained from P. brasiliensis mycelial form cultures, the fungal stage most probably existing in nature. As such, the corresponding experiments would copy the onset and course of the human infection. A large number of experimental studies done by the CIB Medical and Experimental Mycology Unit in a period of almost 25 years have been revised and extracted so as to present a comprehensive record on the immune responses induced when mice are infected intranasally with the conidia. The establishment of this mouse model has permitted the analysis of the immune responses taking place during the early and late stages post-challenge. This unique model has made possible to characterize the course of the experimental disease including the inflammatory reaction, the expression of cytokines and of the various molecules associated to these responses, all of which lead to granuloma formation. The latter structure serves as a nest for the development of fibrosis. Thus, we have also obtained a glimpse on the complexity that accompanies the fibrosis, the most common sequelae of paracoccidioidomycosis. Additionally, a concerted effort has been made to appraise the whole gamut of immune factors and related molecules that directly or indirectly, contribute to shape the pathogenesis of this Latin American mycosis.